2019
DOI: 10.3390/jcm8070981
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Impact of Acute Kidney Injury in Patients Receiving Extracorporeal Membrane Oxygenation: A Meta-Analysis

Abstract: Background: Although acute kidney injury (AKI) is a frequent complication in patients receiving extracorporeal membrane oxygenation (ECMO), the incidence and impact of AKI on mortality among patients on ECMO remain unclear. We conducted this systematic review to summarize the incidence and impact of AKI on mortality risk among adult patients on ECMO. Methods: A literature search was performed using EMBASE, Ovid MEDLINE, and Cochrane Databases from inception until March 2019 to identify studies assessing the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
98
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 108 publications
(145 reference statements)
5
98
3
4
Order By: Relevance
“…Those needs that are classified as unmet require provision of some ample spaces for the purpose of imagination in relation to leveraging the strength associated with big data, as well as relevant artificial intelligence (AI) to improve the overall status of patients with kidney diseases [25]. In this article, we discuss the big data concepts in nephrology, describe the potential use of AI in nephrology and transplantation, and also encourage researchers and clinicians to submit their invaluable research, including original clinical research studies [26][27][28][29][30], database studies from registries [31][32][33], meta-analyses [34][35][36][37][38][39][40][41][42][43][44], and artificial intelligence research [25,[45][46][47][48] in nephrology and transplantation. Table 1 demonstrates known and commonly used databases that have provided big data in nephrology and transplantation [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Those needs that are classified as unmet require provision of some ample spaces for the purpose of imagination in relation to leveraging the strength associated with big data, as well as relevant artificial intelligence (AI) to improve the overall status of patients with kidney diseases [25]. In this article, we discuss the big data concepts in nephrology, describe the potential use of AI in nephrology and transplantation, and also encourage researchers and clinicians to submit their invaluable research, including original clinical research studies [26][27][28][29][30], database studies from registries [31][32][33], meta-analyses [34][35][36][37][38][39][40][41][42][43][44], and artificial intelligence research [25,[45][46][47][48] in nephrology and transplantation. Table 1 demonstrates known and commonly used databases that have provided big data in nephrology and transplantation [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis has demonstrated that the pooled incidence of AKI and severe AKI requiring renal replacement therapy (RRT) among adult patients on ECMO was 63% and 45%, respectively. Furthermore, adult ECMO patients with AKI requiring RRT have a significantly increased mortality with a pooled odds ratio (OR) of 3.73 [11]. Although the incidence and associated mortality of AKI in adults on ECMO are widely reported, comparable data in the pediatric population are limited.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Acute kidney injury (AKI) is a frequent complication of critically ill patients receiving ECMO with the mechanism of injury often being multi-factorial (hemodynamic instability, inflammatory response to the membrane, related to the underlying disease process or pre-morbid conditions). [4][5][6][7] The incidence of AKI in the setting of ECMO is highly variable and depends on the AKI definition employed and indications for ECMO; similarly, a significant number of these patients require renal replacement therapy with rates varying from 25.5% to 67% depending on the cohort. [7][8][9][10][11][12] Kashani and colleagues have recently undertaken a meta-analysis of 41 cohort studies including more than 10,000 patients treated with ECMO; they demonstrated that the incidence rate of AKI remains high (pooled estimate incidence (95% CI) 62.8% (52.1%-72.4%) but has not changed over time.…”
mentioning
confidence: 99%
“…[4][5][6][7] The incidence of AKI in the setting of ECMO is highly variable and depends on the AKI definition employed and indications for ECMO; similarly, a significant number of these patients require renal replacement therapy with rates varying from 25.5% to 67% depending on the cohort. [7][8][9][10][11][12] Kashani and colleagues have recently undertaken a meta-analysis of 41 cohort studies including more than 10,000 patients treated with ECMO; they demonstrated that the incidence rate of AKI remains high (pooled estimate incidence (95% CI) 62.8% (52.1%-72.4%) but has not changed over time. Further, they demonstrated that in an adjusted analysis, patients with AKI requiring RRT (AKI-D) had an adjusted pooled odds ratio (95% CI) of 3.32 (2.21-4.99); I 2 =82% for inpatient mortality compared to those on ECMO who did not require RRT.…”
mentioning
confidence: 99%
See 1 more Smart Citation